Evaluation and comparison of the hepatoprotective effects of trimetazidine and lovastatin against doxorubicin-induced hepatotoxicity - Sikandar, Abeera; Farhat, Kulsoom; Hamza, Amir (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The dosage of highly efficacious anti-cancer drug doxorubicin (DOX) is often constrained as limited data exists on its hepatotoxic potential. The present study not only evaluated the extent of its hepatotoxicity but also aimed at curtailing it, by administration of two drugs i.e. trimetazidine and lovastatin, both of which are otherwise known for their cardioprotective benefits. Methods: The study was a lab-based randomized controlled study on mice. Acute toxicity was introduced with DOX injected intraperitoneally at a dose of 10 mg/kg and it was protected by oral administration of trimetazidine and lovastatin, both in a dose of 10 mg/kg. The protective drugs were both given for five and ten consecutive days in short and long term study designs whereby DOX was administered on the third and eighth days of the respective studies. Results: Doxorubicin administration caused significant hepatotoxicity reflected by markedly raised biomarkers (serum alanine aminotransferase and aspartate aminotransferase) and mild inflammation of liver parenchyma with a score of 4 as per Ishak grading scale. The changes were significantly attenuated by both the protective drugs in the ten days study design. However, in the five days study, lovastatin exhibited more significant hepatoprotection than trimetazidine. Conclusions: Pretreatment with two commonly available, cost effective and safe drugs can effectively prevent a potentially life-threatening adverse effect of DOX. This approach might prove very convenient for the health care providers as well as for the patients without burdening the economics.